Comparison of the Metabolic Characteristics of Newer Second Generation Antipsychotics: Brexpiprazole, Lurasidone, Asenapine, Cariprazine, and Iloperidone With Olanzapine as a Comparator. Issue 1 (January 2021) - Greger, Jessica; Aladeen, Traci; Lewandowski, Emily; Wojcik, Rachael; Westphal, Erica; Rainka, Michelle; Capote, Horacio
Abstract: Purpose/Background: Extensive research has been conducted comparing the metabolic characteristics of older second-generation antipsychotics (SGAs); minimal data exist comparing the long-term metabolic effects of SGAs approved in the last 10 years. Methods/Procedures: A retrospective chart review of patients treated with brexpiprazole, lurasidone, asenapine, cariprazine, and iloperidone (newer SGAs) for at least 6 weeks at an outpatient psychiatric practice was conducted. Patients treated with olanzapine, an older SGA, were included as a comparator. Metabolic characteristics were collected at baseline, approximately 6 weeks, 12 weeks, and for up to 12 months. Findings/Results: Of the newer SGAs, there were statistically significant increases in patients' average weight at 12 weeks and 1 year or less with brexpiprazole (2.48 lb, P = 0.02; 5.97 lb, P = 0.01) and iloperidone (4.54 lb, P < 0.01; 5.13 lb, P = 0.02). Brexpiprazole and iloperidone resulted in significant increases in body mass index, up to a 0.90-kg/m 2 average increase in patients taking brexpiprazole at 1 year or less. Minimal weight gain was seen with cariprazine (4.25 lb, P = 0.42) and asenapine (1.80 lb, P = 0.62) at 1 year or less after treatment initiation. Although not statistically significant, lurasidone showed an average weight loss of up to 0.60 lb at 1 year or less ( P = 0.56). Implications/Conclusions: Although some weight gain was seen with the newer SGAs, all demonstrated significantly favorable metabolic characteristics compared with olanzapine. Monitoring of weight and metabolic parameters remain important in patients treated with SGAs.